볶음처리에 따른 뽕나무 잎차의 생리활성 물질 - 임명자; 배영일; 정창호; 조복래; 최진상; Myung Ja Lim; Young Il Bae; Chang Ho Jeong; Bok Rae Cho; Jine Shang Choi (농업생명과학연구, 2007)
볶음, 유념 및 가향 등의 가공처리를 통하여 제조한 뽕나무 잎차의 생리활성 물질을 조사하였다. 건조한 잎의 수분함량은 11.08%(Aw 0.67) 이었고, 350±50℃에서 10분간 볶음 및 1～5회 유념처리를 한 뽕나무 잎차의 수분 함량은 각각 3.46%와 2.58% (Aw 0.24와 0.13)였다. 플라보놀은 quercetin, kaempferol 및 myricetin이 동정되었으며, 그 중 quercetin이 가장 많이 함유되어 있었고, 볶음, 유념 및 가향처리를 함으로써 감소하는 경향을 보였다. 폴리페놀 화합물들은 총 7종이 함유되어 있었고, 그 중 chlorogenic acid가 4.64±0.24 mg/g, epigallocatechin gallate가 2.10±0.10 mg/g으로 전체의 81%를 차지하였으며, 가공처리(볶음, 유념 및 가향 공정)를 거침에 따라 50%가 감소하였다. 건조한 뽕나무 잎의 rutin 함량은 0.97±0.02 mg/g이었고, 볶음 및 유념을 함으로써 23～30%가 감소하였으나 가향처리에 의해서는 오히려 증가하였다. 건조한 뽕잎의 deoxynojirimycin함량은 4.31±0.12 mg/g였으며, 유념 1회 및 가향처리를 한 시료는 다소 증가하였으나, 유념 5회 및 가향처리를 한 시료에서는 오히려 감소하였다. 뽕나무 잎차의 생리활성 물질은 5회 유념한 시료에 비해 1회 볶음 및 유념한 시료에서 높게 나타났으나 관능검사의 경우 유념 5회 및 가향 처리 공정을 거친 뽕나무 잎차의 색, 맛 향 및 전체적인 기호도면에서 상품성이 높았다. Mulberry(Morus alba) leaf tea was prepared by roasting, crumpling and finishing touches that the tea was roasted and crumpled one to five times. The moisture content was 11.08%(Aw 0.67) in dried mulberry leaf, and mulberry leaf tea decreased to 3.46 and 2.58%(Aw 0.24 and 0.13) that the tea was roasted and crumpled one to five times at 350±50℃ for 10 min. Quercetin, kaempferol and myricetin, were isolated as flavonols and quercetin was higher than others. Flavonols were decreased during roasting, crumbling and finishing touches. Polyphenols were analysed seven varieties in mulberry leaf tea and, chlorogenic acid 4.64 mg/g and epigallocatechin gallate 2.10 mg/g were 81% of them. And also polyphenols decreased 50% during the process(roasting, crumbling and finishing touches). Rutin content showed 0.97±0.02 mg/g in dried mulberry leaf, but decreased during the tea making procedure about 23～30%. However rutin increased after finishing touches. Deoxynojirimycin was 4.31±0.12 mg/g in dried mulberry leaf and slightly increased at just one time roasting and crumbling process, but decreased after repeated five time roasting, crumbling and finishing touches. Phytochemical components were much in tea just one time roasting and crumbling process than five treatment mulberry leaf tea, but showed poor an article on a commercial scale. However in tea five time roasting, crumbling and finishing touches, color, taste, flavor and overall preference were best of them. KCI Citation Count: 7